Live Streaming TikTok Sebagai Strategi Komunikasi Pemasaran Pada Brand Skincare - Jacob, Delicia Regina (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research investigates using TikTok live streaming as a creative marketing communications strategy in the skin care industry. The research method used is descriptive qualitative with a basis in marketing communication theory and new media concepts. Through interviews and focus group discussions, this research explores how the skincare brand